Implementation of the Merdeka Curriculum to Strengthen Literacy Skills in Early Grades of Elementary Schools - Marzoan, Marzoan (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study discusses the implementation of the Kurikulum Merdeka as a strategic step to strengthen literacy skills in early grades at Elementary Schools. The research aims to investigate and analyze the implementation of the Kurikulum Merdeka, identify potential challenges, and evaluate its impact on strengthening literacy skills of students in elementary schools. The research method employed a qualitative approach with a focus on the experiences of students, teachers, and school principals. The study took place in 20 elementary schools across 4 districts implementing the Kurikulum Merdeka in Central Lombok Regency, West Nusa Tenggara. Data collection involved interviews and observations of the implementation of initial assessments and differentiated learning, which are integral parts of the Kurikulum Merdeka. The findings reveal that the majority of teachers have conducted initial assessments in accordance with Kurikulum Merdeka procedures. Although there are challenges related to the understanding of guidelines by a small percentage of teachers, there are strong indications of a shift in their mindset regarding the importance of assessments. Differentiated learning is implemented in various ways, with students experiencing its benefits, including improved literacy skills. Schools also have data-based literacy reinforcement programs to support the implementation of the Kurikulum Merdeka. The conclusion of this study is that the implementation of the Kurikulum Merdeka in terms of assessment and differentiated learning has a positive impact, including the potential to enhance students' literacy skills. Despite challenges, continuous efforts are being made to improve the quality of learning and literacy achievements of students. The results of this research provide valuable insights for education practitioners and policymakers to continually enhance the effectiveness of the Kurikulum Merdeka in shaping a smart and competitive younger generation in the current era and the future.